2019
DOI: 10.1021/acs.biomac.9b00512
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Amorphous Hydrophilic Block Affects Self-Assembly of an Artificial Viral Coat Polypeptide

Abstract: Consensus motifs for sequences of both crystallizable and amorphous blocks in silks and natural structural analogues of silks vary widely. To design novel silklike polypeptides, an important question is therefore how the nature of either the crystallizable or the amorphous block affects the self-assembly and resulting physical properties of silklike polypeptides. We address herein the influence of the amorphous block on the self-assembly of a silklike polypeptide that was previously designed to encapsulate sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…A final mild bake-out procedure was sufficient to further purify the desired proteins to an acceptable level (Figure 6a). As previously observed, 57,58 the poor SDS-binding of ELPs leads to anomalously high molecular weights in SDS-PAGE when compared with globular protein molecular weight standards. To confirm the identity of the polypeptides, MALDI-TOF spectra were determined for the purified proteins (Figure 6b).…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…A final mild bake-out procedure was sufficient to further purify the desired proteins to an acceptable level (Figure 6a). As previously observed, 57,58 the poor SDS-binding of ELPs leads to anomalously high molecular weights in SDS-PAGE when compared with globular protein molecular weight standards. To confirm the identity of the polypeptides, MALDI-TOF spectra were determined for the purified proteins (Figure 6b).…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…[ 32 ] Previous studies have demonstrated that polymer chains with certain rigidity and orientation can accelerate the folding of SF secondary structure. [ 33 ] Therefore, we wondered what effect the introduction of MMP‐9 sensitive gelatin could have on the self‐assembly of SF, considering the typical rigid tri‐helix structure of gelatin. Excitingly, we observed an obvious microphase separation in the Gel/SF mixed solution under gentle ultrasound, as observed via liquid‐phase scanning microscopy (LSM) and atomic force microscope (AFM) ( Figure ai,ii).…”
Section: Resultsmentioning
confidence: 99%
“…In the study published by Luo and Kiick, 100 The study published by Willems et al 102 investigates the influence of the amorphous or crystallizable block on SA of a silk-like triblock polypeptide that was previously designed to encapsulate single DNA molecules to give rise to rod-shaped virus-like particles (VLPs). This polypeptide has a triblock architecture consisting of a long Nterminal amorphous block, a crystallizable middle block, and a Cterminal DNA-binding block.…”
Section: Collagen-likementioning
confidence: 99%